Provenance ages of late Paleozoic sandstones (Santa Rosa Formation) from the Maya block, SE Mexico. Implications on the tectonic evolution of western Pangea - Bodo Weber; Peter Schaaf; Victor A. Valencia; Alexander Iriondo; Fernando Ortega-Gutiérrez (Revista Mexicana de Ciencias Geológicas)
The Santa Rosa Formation in the State of Chiapas is a sequence of flysch-type sediments of Mississippian to Pennsylvanian age. These sedimentary rocks correlate with the Santa Rosa Group of Guatemala and Belize and crop out along the southern limit of the Maya block north of the Motagua fault, which is currently considered the border between the North American and the Caribbean plates. Ages of individual zircon grains from sandstones of the Upper Santa Rosa Formation in southern Mexico were analyzed by Laser Ablation Multicollector ICPMS and by SHRIMP. The youngest zircon population is of Silurian age (~420 Ma), but most grains have ages that correspond to the Pan-African-Brasiliano orogenic cycle (500–700 Ma). Other minor populations have ~820 Ma, Grenville (1.0–1.3 Ga), Mesoproterozoic (1.4–1.6 Ga), Paleoproterozoic (1.8–2.2 Ga), and Archean (2.7–3.1 Ga) ages. Most of the sediments came from either present-day West Africa or NE South America, where both Pan-African-Brasiliano orogens and cratonic landmasses are present. In our model, southwestward progressive collision of Gondwana with Laurentia during the Alleghanian orogeny resulted in erosion and deposition of flysch-type sediments to the west, followed by westward movement of the Maya block and adjacent lithosphere.